2011
DOI: 10.1525/sop.2011.54.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Social Class, and Exclusion: Collegiate Peer Cultures and Social Reproduction

Abstract: This article explores gender and class exclusion among college students. The authors use qualitative data to explore how students talk about gender and class exclusion and quantitative data to model.patterns of exclusion within the Greek system. The Greek system serves as a site for social reproduction. Students constructed young women as elitist and prone to class exclusion, while typifying young men as unconcerned with such matters. Quantitative analyses complicate these findings. Within the Greek system, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Prior research revealed that class-privileged parents often enroll their children and adolescents in a wide variety of time and resource-intensive organized activities [31]. This parenting style is largely motivated by the belief that extracurricular engagement plays a vital role in enabling children to become well-rounded and passionate individuals, which increases their chances of getting into elite colleges and companies [47]. By contrast, prior studies found that less-privileged parents often believe that extracurricular involvement matters less than academic achievements and job-related skills in educational institutions and workplaces [4,46].…”
Section: Industrial Fit: Ties To Social Class Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research revealed that class-privileged parents often enroll their children and adolescents in a wide variety of time and resource-intensive organized activities [31]. This parenting style is largely motivated by the belief that extracurricular engagement plays a vital role in enabling children to become well-rounded and passionate individuals, which increases their chances of getting into elite colleges and companies [47]. By contrast, prior studies found that less-privileged parents often believe that extracurricular involvement matters less than academic achievements and job-related skills in educational institutions and workplaces [4,46].…”
Section: Industrial Fit: Ties To Social Class Backgroundmentioning
confidence: 99%
“…Scholars have revealed that parents generally transmit their class-based beliefs about the importance of social and extracurricular activities to their children [40,47]. In the context of securing employment, prior research found that applicants from class-privileged upbringing largely focus on connecting with professionals at recruitment events [40].…”
Section: Industrial Fit: Ties To Social Class Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraternities and sororities can be locations of substantial social reproduction, particularly regarding issues of privilege (Stuber, Klugman, & Daniel, ). External construction of social reproduction by nonmembers depicts women as more concerned about elitism than men, while some studies demonstrate men within fraternities to be more concerned with preservation of privilege (Stuber et al, ). A troubling element in much of the research is the extent to which stereotypes, rather than models or theories, are used as the foundation for creating research instruments or analysis.…”
Section: Psychosocial Effectsmentioning
confidence: 99%
“…For example, in both elite boarding school and college cultures and in more working-class educational environments, womens and girls' bodies are the stage for communicating class-specific definitions of feminine desirability. In elite school settings, cultivated slimness, expensive brand-name clothing, jewelry, and purses signal feminine desirability (Chase 2008;Gaztambide-Fernandez 2009;Khan 2010;Stuber, Klugman, and Daniel 2011). In lower-class settings, the accoutrement of femininity may be less expensive or luxurious (Bettie 2003), but being sexually desirable to men is just as valued.…”
Section: The Idealized Relationship Between Masculinity and Femininitymentioning
confidence: 99%